Accounting Conservatism in Family Businesses: An Ethnographic Study of Guanxi in Samarinda Shipping Company - Nurul Permatasari, Rika; Juanda, Ahmad; Rumijati, Aniek (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study aims to analyze how accounting conservatism is practiced in a Chinese family-owned shipping company in Samarinda, Indonesia, by exploring the influence of guanxi culture through an ethnographic approach. Guanxi, representing trust, loyalty, reciprocal obligations, and interpersonal harmony, shapes financial decision-making, reporting behavior, and risk assessment in business. The findings suggest that conservatism is not simply an accounting choice, but rather a cultural mechanism to maintain relationship harmony, minimize future uncertainty, and preserve family wealth. This study contributes to the behavioral and cultural accounting literature by demonstrating that accounting practices are embedded in local cultural logic and that family businesses rely on conservative reporting to ensure economic and relationship stability.